Analysis of the Impact of Sewage Outfall on the Water Quality of Coastal Waters of Macau Based on MIKE21 Model - CHANG Ze; ZHANG Qionghai; JIANG Yu; SUN Ning; HE Rui; WANG Tengfei; WU Yaju; LONG Xiaofei (Renmin Zhujiang)
This paper simulates the impact of the sewage outfall of the Macau Taipa Wastewater Treatment Plant on the water quality changes in the nearby Lingding Ocean by the hydrodynamic module (HD) and the transmission diffusion module (TR) of the MIKE21 model,provides the boundary conditions for the local two-dimensional tidal current model (built by MIKE21) through the one and two-dimensional integrated tidal current model of the Pearl River Estuary area,and analyzes the impact of pollutant diffusion under normal discharge and accident discharge in terms of the three evaluation factors,namely CODCr (chemical oxygen demand),SS (total suspended solids) and NH3-N (Ammonia-Nitrogen),under the “2005·6” flood combination and “2001·2” low water combination as the most unfavorable hydrological conditions.The results show that the water quality of main channel can meet the Class Ⅲ standard among the Sea Water Quality Standards (GB 3097—1997).With proper preventive measure,the out-of-limit water area under accidental discharge is less than 0.2 km2.This model has good adaptability to the simulation of the diffusion of pollutants into the coastal waters of Macau,so it can better simulate the impact of sewage discharge on the water quality of the sea under the action of ocean tides,and serve as a basis and research direction for the establishment of sewage outfall.